Membranous Nephropathy-Like Apolipoprotein E Deposition Disease with Apolipoprotein E Toyonaka (Ser197Cys) and a Homozygous Apolipoprotein E2/2 - Megumu Fukunaga (Case Reports in Nephrology and Dialysis, 2018)
A 20-year-old female student underwent renal biopsy because of chance proteinuria and hematuria. Histological study revealed a membranous nephropathy-like appearance by light microscopy. But immunoglobulins and complements were negative in the glomerulus by immunofluorescence study. On the other hand, plasma apolipoprotein E (ApoE) concentration was elevated to more than 2 times the normal range, and the phenotype, genotype, and DNA sequence studies of her ApoE showed homozygous ApoE2/2 and a heterozygous novel missense mutation called ApoE Toyonaka (Ser197Cys). Detailed immunohistochemical studies found that the dense deposits in subepithelial, subendothelial, and mesangial areas contained ApoE. Tandem mass spectrometry also proved a large amount of ApoE in the glomerulus. These findings suggest that ApoE Toyonaka with a homozygous ApoE2/2 may cause a new form of ApoE-related glomerular disease resembling membranous nephropathy.